2009
DOI: 10.1111/j.1744-697x.2009.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Root and rhizome systems of perennial grasses grown in Inner Mongolian grassland, China

Abstract: The root and rhizome systems of dominant perennial grasses in Inner Mongolian grassland were clarified. We surveyed the vertical distribution of root and rhizome biomass in the natural stands, and the changes of under‐ground biomass and the branching pattern of rhizomes for transplanted plants in a container experiment. Most roots of Leymus chinensis, Bromus inermis, Elymus dahuricus and Agropyron cristatum were distributed in the soil depth of 0–10 cm. Roots of E. dahuricus and A. cristatum were distributed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A. cristatum is a bunch‐forming grass lacking rhizomes, whereas B. inermis is a sod‐forming grass that propagates both via rhizomes and seeds (Ao et al . ). Although they showed similar germination characteristics, the role of propagation via seeds in the whole population cycle differs between these species.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A. cristatum is a bunch‐forming grass lacking rhizomes, whereas B. inermis is a sod‐forming grass that propagates both via rhizomes and seeds (Ao et al . ). Although they showed similar germination characteristics, the role of propagation via seeds in the whole population cycle differs between these species.…”
Section: Discussionmentioning
confidence: 97%
“…L. chinensis is a dominant species of the natural grassland of this area, and forms a dense sod through its extensive rhizome system (Ao et al . ). Liu and Han () experimentally showed that a vegetation gap is required for the successful emergence and establishment of L. chinensis seedlings, and they reported that the requirement for a fluctuating temperature for germination is a gap‐detecting mechanism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Belowground properties in areas dominated by crested wheatgrass have also been examined. Compared with native perennial grasses, crested wheatgrass has been shown to contribute less carbon and nitrogen to the soil in root exudates (Biondini et al, 1988), root biomass can be similar (Broersma et al, 2000) or lower (Smoliak & Dormaar, 1985;Christian & Wilson, 1999), and roots are typically coarser and inhabit shallower depths (Dormaar et al, 1995;Ao et al, 2009). As a result of lower root inputs, soils beneath crested wheatgrass stands may contain lower amounts of organic matter (Dormaar et al, 1995), less mineral and total nitrogen, and less total carbon (Christian & Wilson, 1999) than those beneath native perennial grass stands.…”
Section: Introductionmentioning
confidence: 99%